Penguatan Kompetensi Teknologi dan Solidaritas Sosial melalui Perspektif Sosiologi Pendidikan di SMA Usdatara - Manuhutu, Melda Agnes; Leuwwol, Natasya; Uktolseja, Lulu Jola; Siagian, Dewi; Delfin, Delfin; Desi, Desi; Gilber, Gilber; Lazarus, Lazarus; Yohana, Yohana; Yoland, Yoland (CV. Era Digital Nusantara, 2026)
The student empowerment program through computer network cabling training at SMA Usdatara was implemented to enhance technological competence while strengthening social solidarity within the school environment. From the perspective of sociology of education, this activity not only focused on developing students’ technical skills but also emphasized collaboration, interaction, and the formation of positive social relationships throughout the learning process. The program was carried out by a team of university students through stages of observation, socialization, training, and evaluation, engaging participants actively in hands-on cable assembly, device introduction, and group-based practice. The results indicate that the training generated dual impacts. In terms of technological competence, students gained a better understanding of basic computer network concepts and were able to practice proper cabling techniques. Socially, the activity enhanced solidarity through teamwork, peer assistance, and cooperative communication during practical sessions. The interactions between university students and high school participants also demonstrated a dialogical and participatory learning process, in which social experiences played an essential role. Overall, this program shows that technology-based empowerment can simultaneously serve as a means of fostering constructive social bonds within the school community